The education system in Malawi (World Bank, 2010)
Demographics, social development, and macroeconomic conditions – Enrollment patterns – Education expenditure and financing – Internal efficiency, learning outcomes, and management issues – Equity and disparities – Technical, entrepreneurial, and vocational education and training – Higher education – External efficiency
Literaturverz. S. 335 - 340
Keywords: Arbeitspapier; Graue Literatur; Bildungswesen; Malawi; Education